2017
DOI: 10.3747/co.24.3677
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Practice in Definitive Chemoradiation for Localized Esophageal Cancer

Abstract: BackgroundThe efficacy of carboplatin-paclitaxel in the trimodality setting was demonstrated in the cross

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
10
2
Order By: Relevance
“…However, it should be noted these studies used docetaxel–cisplatin, whereas we used paclitaxel–carboplatin. In contrast to our findings, Qu et al (2017) reported that PF ( n = 34) was superior to PC ( n = 26) in inoperable EC 17 . Moreover, some studies found similar outcomes between PF and PC in concurrent CRT 14‐16,19,21 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, it should be noted these studies used docetaxel–cisplatin, whereas we used paclitaxel–carboplatin. In contrast to our findings, Qu et al (2017) reported that PF ( n = 34) was superior to PC ( n = 26) in inoperable EC 17 . Moreover, some studies found similar outcomes between PF and PC in concurrent CRT 14‐16,19,21 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the setting of dCRT, CP seemed to yield significantly inferior survival, with an HR >3 despite adjusting for age and radiotherapy doses received and additional baseline characteristics using IPTW modeling. The OS data for the dCRT subcohort mirror results from previous reports [12]. The drastically inferior outcomes of the CP regimen seen highlight the need for caution before adopting CP as a preferred approach in dCRT.…”
Section: Discussionsupporting
confidence: 78%
“…While dCRT of 50 Gy with CF is established as the standard of care [6, 7], CP has been increasingly utilized without supporting prospective data [12] in accordance with recommendations by the US NCCN guideline [8]. The literature comparing CP to CF has been extremely limited for Western patients receiving dCRT, with two comparative retrospective studies, to our knowledge, which published mixed results [12-14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboplatin-paclitaxel is considered more tolerable than platinum-fluoropyrimidine based on comparison of the CROSS trial with historical controls (ie, RTOG 8501 and Intergroup [INT] 0123) and retrospective studies. 1 , 23 , 24 , 25 The ongoing PReoperative Chemoradiation for Resectable Esophageal and Junctional Cancer (PROTECT-1402) phase II trial will compare preoperative folinic acid, 5-FU, and oxaliplatin to carboplatin-paclitaxel. 26 Single-agent chemotherapy typically is considered noncurative 27 ; notably, 20% of our study population received fluoropyrimidine alone.…”
Section: Discussionmentioning
confidence: 99%